Reduced size-independent mechanical properties of cortical bone in high-fat diet-induced obesity - Ionova-Martin, S. S. (Bone, 2009)
Overweight and obesity is a rapidly expanding health problem in children and adolescents. Obesity is associated with greater bone mineral content that might be expected to protect against fracture, which has been observed in adults. Paradoxically however, the incidence of bone fractures has been found to increase in overweight and obese children and adolescents. Prior studies have shown some reduced mechanical properties as a result of high-fat diet (HFD) but do not fully address size-independent measures of mechanical properties, which are important to understand material behavior. To clarify the effects of HFD on the mechanical properties and microstructure of bone, femora from C57BL/6 mice fed either a HFD or standard laboratory chow (Chow) were evaluated for structural changes and tested for bending strength, bending stiffness and fracture toughness. Here we find that in young obese high fat fed mice all geometric parameters of the femoral bone, except length, are increased but strength, bending stiffness and fracture toughness all are reduced. This increased bone size and reduced size-independent mechanical properties suggests that obesity leads to a general reduction in bone quality despite an increase in bone quantity; yield and maximum loads, however, remained unchanged, suggesting compensatory mechanisms. We conclude that diet-induced obesity increases bone size and reduces size-independent mechanical properties of cortical bone in mice. This study indicates that bone quantity and bone quality play important compensatory roles in determining fracture risk.